Cold chain evaluation of the immunization program in Primary Health Centers in 2022 - Isworo, Adi; Kiswoyo, Pramono Giri; Suharsono (BKM Public Health and Community Medicine, 2024)
Purpose: The major challenges of vaccination programs are associated with the vaccine cold chain management in primary health centers that must be evaluated. This paper discusses how vaccine cold chain management can address the challenges of vaccination programs in primary health centers. Specifically, it examines how the vaccine chain is managed. Methods: The design of this observational study was cross-sectional. Evaluations assessed in this study include input aspects, output aspects, process aspects, and outcome aspects of vaccine chain management. Observation methods and direct interviews with the evaluated vaccine chain staff collected primary data. Results: Management of the vaccine chain has been carried out properly with the support of human resources or immunization personnel who are in accordance with their competence, based on research results, the management staff are diploma graduates in nursing and midwifery. The defrosting process is carried out for a certain period, as well as using vaccine carriers and ice flasks, which are still good for vaccine distribution. It is very important to pay attention to the supply of the number and type of vaccines for the next month's needs at the public health center. Conclusion: The three key factors that guide the vaccine cold chain are educated vaccine control staff, vaccine storage, and delivery equipment, and efficient vaccine control procedures.